The Potential Role of Human Herpes Virus-6 in Idiopathic Facial Nerve Paralysis (Iraqi Journal of Medical Sciences, 2021)
Background:Bell’s palsy (BP) is an acute, generally unilateral, paralysis or weakness of facial musculature consistent with peripheral facial nerve dysfunction; different factors suspected to contribute to the development of BP including herpesviruses.Objective:To detect human herpes virus 6 (HHV-6) in the saliva samples of patients in the early presentation of BP.Methods: A case-control study included saliva samples taken from 50 patients with BP and 50 apparently healthy controls without any neurological deficit, viral DNA was extracted from the saliva and then subjected for quantitative real time polymerase chain reaction (PCR) for detection of HHV-6 viral load (VL) in saliva.Results: HHV-6 DNA was positive in 22 (44%) out of the 50 patients, and in 12 (24%) of the controls (p=0.028), with a significantly higher mean viral load in patients than control (p=0.002), in addition, 70% of HHV-6 positive patients had severe grades with a significantly higher VL (p=0.007) and (0.015), respectively.Conclusion: HHV-6 could play an important role in the development of BP and HHV-6 might have a neuro-pathological effect in severe cases of BP.Keywords: HHV-6, Bell's palsy, Saliva, real time PCRCitation: Rhaif RH, Al-Obaidi AB, Al-Khazrajee AK. The potential role of Human Herpes Virus-6 in idiopathic facial nerve paralysis. Iraqi JMS. 2020; 18(1): 47-51. doi: 10.22578/IJMS.18.1.7
Keywords: HHV6; Bells palsy; Saliva; real time PCR